Empirical Equations (Biological Examples) - Whittembury M., Guillermo (1957)
This is specific to the study of empirical equations and is the first of a series of publications that seek to spread the quantitative method in studies of biology and medicine. One of their most important problems of scientific work is when you have to measure, establish and describe relationships between variables; most of the established scientific laws.